Penilaian Status Frailty Berbasis Komunitas pada Festival Lansia 2026 di Kabupaten Lombok Timur - Lalu Suprawesta; Indri Susilawati; Hayyu Fathil Hasanah; Abdul Bashir Nur Hasani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Frailty is a geriatric syndrome characterized by a decline in physiological capacity, thereby increasing the vulnerability of the elderly to falls, disability, loss of independence, and reduced quality of life. However, the assessment of frailty status is rarely integrated into community-based health activities. This community service initiative aimed to characterize the frailty status and physical condition profiles of elderly individuals using a community-based assessment model that integrated the FRAIL Scale, physical function assessments, and individualized health education during the 2026 Elderly Festival in East Lombok Regency. The activity employed a community-based participatory approach involving lecturers, physiotherapists, volunteers, and the Rumah Senja Foundation. A total of 21 elderly participants underwent demographic data collection, FRAIL Scale assessment, grip strength measurement using a handgrip dynamometer, lower-extremity function assessment using the Five Times Sit-to-Stand Test (5xSTS), and health education tailored to their individual assessment results. The results indicated that 61.9% of participants fell into the pre-frail category and 38.1% into the frail category, with no participants classified as robust. The most dominant FRAIL Scale components were resistance (71.4%), followed by fatigue (57.1%) and illness (52.4%). Although most participants retained normal grip strength, more than half of the pre-frail (53.9%) and frail (62.5%) participants exhibited reduced lower-extremity function based on the 5xSTS. The high proportion of participants in the pre-frail and frail categories highlights the importance of early detection coupled with community-based promotive and preventive interventions to maintain physical function and prevent the progression of frailty. This initiative demonstrates that an integrated assessment model has the potential to support the development of community-based elderly health services oriented towards healthy aging and the preservation of elderly independence.